Short-term variations in ambient particulates and their sources in Taichung, Taiwan. (7th September 2004) - Fang, Guor-Cheng; Wu, Yuh-Shen; Huang, Winn-Jung; Lu, Hsin-Chung; Fu, Peter; Chen, Yuh-Shuen
Ambient particulate measurements were carried out using TE-PUF sampling and a Universal Air Sampler between 8 March and 25 April 2001 at Taichung. Samples were collected every 6 hours beginning at 0100 LST (Local Standard Time) each day at two sites, one at a university campus and the other at a roadside. Chemical species (Cl -, NO3 -, SO4 2-, Na +, NH4 +, K +, Mg 2+, Ca 2+, Fe, Zn, Pb, Ni) were analysed simultaneously. The main sources at the campus sampling site were identified as soil dust re-suspension, sea salt spray, secondary aerosols and zinc-related industry, and those at the traffic sampling site as soil dust re-suspension, sea salt spray, secondary aerosol and fuel combustion. The diurnal variation of all the chemical species' concentrations were also measured. The meteorological conditions and the pollutant emission sources near the sampling sites are likely impact factors. These results also showed that the short-term diurnal variation of the concentrations of chemical species in the ambient suspended particulates is useful to identify the sources and modes of formation of the particulates.